Produção de gérberas de vaso em resposta a adubos orgânicos líquidos obtidos de compostos de resíduos agroindustriais - Koelln, Francielly Torres dos Santos (2012)
The commercial production of flowers and ornamental plants in Brazil has increased worldwide. Gerbera has been highlighted among the most commercialized flowers; however, studies concerning its management are still needed, especially in Brazil. Thus, this study aimed at evaluating fertilization with agribusiness waste, applied as liquid organic fertilizer (fertirrigation) to produce gerbera (Gerbera jamesonii) in pots as well as monitoring the development and quality of Florist Red Black cultivar. The statistical design was in randomized blocks with four replications and five treatments. The potted seedlings were carried out in a commercial substrate. The treatments were: mineral fertilizer and four treatments with different organic compositions using fertirrigation. The liquid organic fertilizers were chemically characterized according to pH, electrical conductivity, macro and micronutrients. The irrigation of mineral treatment was carried out with water and the organic treatments were irrigated with liquid organic fertilizers, both were carried out according to the crop evaporation. During this study, the number of leaves, plant diameter, dry mass of aerial part, analyses of development and concerning nutrient content in leaves, pH and electric conductivity of substrate solution were recorded. At the sale moment, some characteristics were evaluated, as: plant height, plant diameter, head diameter, diameter of flower stalks, inflorescence height and number of inflorescences. A sensorial analysis was used at the sale point to evaluate the visual quality of plants according to the discriminative and affective method, as for ornamental plants, the best obtained results by the metrics analysis mostly do not reflect plants with the best aesthetic characteristics. Considering the obtained data in this study, it was concluded that the liquid organic fertilizer, when applied at a suitable pH to produce gerbera, improved development and visual quality of plants with suitable features for trading. The liquid organic fertilizer in the composite number 4 provided the highest averages of phytometric parameters at the sale moment and sensory analysis.